Sintered porous body having multiple layers

Porous sintered bodies with multiple layers of metal particles address the challenges of filtering supercritical fluids by providing effective filtration and structural support at high temperatures and pressures, enhancing the efficiency and durability of filtration processes.

JP2025514135AActive Publication Date: 2025-05-02ENTEGRIS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024563025
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-04-28
Publication Date
2025-05-02
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

Existing methods for filtering supercritical fluids, such as supercritical carbon dioxide, face challenges due to the stringent high-temperature and high-pressure conditions required, which demand stable and durable filter membranes that can maintain effectiveness over a useful operating lifetime.

Method used

The development of porous sintered bodies with multiple layers made from different metal particles, where the first layer provides structural support and high flow properties, and the second layer acts as a filtering and reinforcing layer, effectively removing nanoscale contaminants from fluids across a wide range of temperatures and pressures.

Benefits of technology

The described porous sintered bodies are effective as filter membranes for various fluids, including supercritical carbon dioxide, maintaining high filtering efficiency and structural integrity even at extreme conditions, thus addressing the limitations of existing filtration technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514135000001_ABST
    Figure 2025514135000001_ABST
Patent Text Reader

Abstract

Inorganic porous sintered bodies that contain multiple layers made from different types of metal particles and that can be useful as filter membranes, and methods for making and using the inorganic porous sintered bodies, are described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to inorganic porous sintered bodies that include multiple layers made of different metal particles and that may be useful as filter membranes, as well as methods of making and using the inorganic porous sintered bodies. [Background technology]

[0002] Porous sintered bodies are used in various industrial applications, including the use of the porous sintered bodies as filter membranes to remove contaminants from fluids used in manufacturing. Many manufacturing processes require very pure fluids, either as raw materials or as processing fluids. For example, many different phases of semiconductor and microelectronic device manufacturing require the use of highly pure gases or liquids as raw materials, as well as highly pure processing fluids for processes such as cleaning, etching and other surface or material preparation processes. In order to provide highly pure fluids during manufacturing, inorganic porous membranes are often used as filter elements to remove contaminants from the fluid immediately prior to its use.

[0003] The fluid may be in the form of a gas, liquid, or supercritical fluid. Supercritical carbon dioxide has a variety of applications in industry, such as cleaning, drying, and solvent extraction applications. Highly pure supercritical carbon dioxide can be used in the electronics and semiconductor manufacturing industries, which require very high degrees of cleanliness and material purity. In one such application, supercritical carbon dioxide can be used to remove photoresist material from the surface of a semiconductor wafer and dry the wafer. Typically, sources of supercritical carbon dioxide are filtered prior to use to remove particulate impurities at low nanoscale levels, for example, by filtering to remove particles in the size range of 10 or 20 nanometers, or smaller.

[0004] Carbon dioxide (CO2) exists as a supercritical fluid at temperatures and pressures above its critical temperature (31.10°C, 87.98°F, 304.25K) and critical pressure (7.39 MPa, 72.9 atmospheres, 1,071 pounds per square inch, 73.9 bar). Typical operating conditions for processes to filter supercritical carbon dioxide include temperatures in excess of 70, 90, or 100 degrees Celsius, and pressures in excess of 25, 30, 35, or 40 Megapascals (MPa).

[0005] Equipment used to process supercritical carbon dioxide must function at the temperatures and pressures required to maintain carbon dioxide in a supercritical state. These conditions are significantly more stringent than those used to filter many other types of industrial raw materials or process fluids. Many processes for filtering other fluids are carried out at ambient or only slightly elevated temperatures and at pressures that are about atmospheric, slightly above atmospheric, or well below atmospheric pressure. Developing new, useful, and improved methods and equipment for filtering supercritical fluids such as supercritical carbon dioxide can be particularly challenging because the equipment and components, such as filter membranes, must be stable and durable at relatively high pressures and temperatures over their useful operational life. Summary of the Invention

[0006] The following description relates to novel inventive porous sintered bodies, filter membranes, methods for preparing the porous sintered bodies, and methods for using the porous sintered bodies as filter membranes.

[0007] The porous sintered membrane comprises two (at least) layers made of sintered inorganic particles, namely a first layer derived mostly or entirely from a combination of coarse and fine particles, and a second layer derived mostly or entirely from a combination of fine and nano particles. The first layer essentially serves as the structural basis of the support for the multilayer membrane, exhibiting high flow properties, as well as sufficient strength and structure to support the second layer. The second layer serves as a filtering layer and as a reinforcing layer. The second layer contains fine particles and nano particles, which combine to form the second layer effective for filtering applications while also contributing to the overall strength of the multilayer membrane.

[0008] The described porous sintered bodies can be effective as filter membranes for filtering a variety of different fluids and over a wide range of temperatures and pressures. The fluids can be gases, liquids, or fluids in a supercritical state. The pressures can be ambient, elevated, or reduced. And the temperatures can be ambient, elevated, or reduced. As a specific example, certain currently preferred porous sintered bodies can be useful as filter membranes for filtering fluids at relatively high temperature and pressure conditions, as well as methods for filtering supercritical fluids such as supercritical carbon dioxide.

[0009] In one embodiment, the present disclosure relates to a porous membrane. The membrane comprises a first layer containing a combination of sintered inorganic particles, including coarse particles with a particle size of at least 10 microns and a coarse particle sintering point, and a first fine particle with a particle size of at least 1 micron and a first fine particle sintering point that is less than the coarse particle sintering point. The membrane also comprises a second layer containing a combination of sintered inorganic particles, including second fine particles with a particle size of at least 1 micron and a second fine particle sintering point that is less than the coarse particle sintering point, and nanoparticles with a particle size of less than 1 micron and a nanoparticle sintering point that is greater than the first fine particle sintering point and greater than the second fine particle sintering point.

[0010] In another aspect, the present disclosure relates to a method of forming a porous membrane, comprising: preparing a precursor comprising a first blend of inorganic particles, the first blend comprising a coarse particle having a particle size of at least 10 microns and a coarse particle sintering point, and a first particulate having a particle size of at least 1 micron and a first particulate sintering point less than the coarse particle sintering point; and applying a second blend of inorganic particles to a surface of the precursor, the second blend comprising a second particulate having a particle size of at least 1 micron and a second particulate sintering point less than the coarse particle sintering point, and a nanoparticle having a particle size less than 1 micron and a nanoparticle sintering point greater than the first particulate sintering point and greater than the second particulate sintering point.

[0011] In another aspect, the present disclosure relates to a tubular porous membrane. The membrane comprises coarse particles having a particle size of at least 10 microns, fine particles having a particle size of at least 1 micron, and nanoparticles having a particle size of less than 1 micron. The membrane has a bubble point of at least 30 pounds per square inch as measured by ASTM E 128-99 (2019) using 60 / 40 isopropyl alcohol (IPA) / water; an air flux value of at least 0.07 slpm / cm2 at 30 psi; and a radial crush test value of at least 35 kilopounds per square inch as measured using ASTM B939-21. [Brief description of the drawings]

[0012] [Figure 1] 1 is a schematic diagram showing a cross-sectional view of a metal porous body of the described examples. This schematic diagram is illustrative and not necessarily to scale. [Diagram 2] 1 is a micrograph of a metal porous body of the described example. [Diagram 3] 1 shows an example of the described filter assembly, including a filter housing and a multi-layer porous sintered body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Described below are novel inorganic porous sintered bodies (e.g., referred to herein as "porous bodies," "porous sintered bodies," or sometimes simply "membranes" or "bodies") that may be useful as filter membranes for filtering fluid flows to remove small-scale, e.g., nanoscale, impurities from the fluid.

[0014] The described porous sintered body is in the form of a porous inorganic body containing two layers, each layer being made to contain sintered inorganic particles. The first layer is derived mostly or entirely from a combination of coarse and fine particles. The second layer is derived mostly or entirely from a combination of fine and nano particles. Each layer is composed of a matrix containing the described inorganic particles, interconnected at the surface of the particles by a sintering process.

[0015] The first layer essentially serves as a structural basis for the support for the multilayer membrane, exhibiting high flow properties, as well as sufficient strength and structure to support the second layer. The second layer functions as a filtering layer and as a reinforcing layer. To provide both strength and filtering functions, the second layer contains two types of particles, namely microparticles and nanoparticles, which combine to form a second layer that performs filtering functions while also increasing the strength of the multilayer membrane. The microparticles in the second layer provide a porous structure within which the nanoparticles are contained and supported. The microparticles of the second layer provide structure and strength. The nanoparticles provide a filtering effect by providing a matrix that defines very small pores that can remove small-scale contaminants (e.g., nanoscale contaminants) from the fluid passing through the second layer.

[0016] Porous sintered bodies are porous inorganic structures that contain a matrix derived from, and are therefore referred to as "including" (e.g., comprising, consisting of, or essentially of) inorganic (e.g., metal, ceramic) particles that are connected together (e.g., "interconnected") at their surfaces by a process of sintering the particles. The particles are fused or bonded together at contacting surfaces to form the interconnected matrix by a process of sintering a precursor containing different types of inorganic particles in an unsintered, optionally compressed, state.

[0017] The term "sintering" as used herein has the same meaning as given to it when used in the art of porous sintered structures, such as the type of porous sintered inorganic membranes that can be useful as metal filter membranes. Consistent therewith, the term "sintering" can be used to refer to the process of bonding together (e.g., "welding" or "fusing") a collection of small inorganic particles of one or more different types (sizes, compositions, shapes, etc.) by applying heat to a green body containing the particles (e.g., "precursors"), whereby the particles reach a temperature at which the particles are fused together, i.e., welded together, by material bonds between the surfaces of adjacent particles, but do not melt the particles, i.e., the particles do not reach a melting temperature or become a flowable liquid.

[0018] As used herein, the "sintering point" or "sintering temperature" of an aggregate of inorganic particles is the temperature at which the particles can be sintered, i.e., the temperature at which the particles within an aggregate of particles having surfaces in contact with each other can be fused together at a certain pressure, such as atmospheric pressure, without melting. The sintering point of an inorganic particle is usually below the melting temperature of the particle, and refers to the temperature at which the material of the particle becomes liquid. The sintering point of an aggregate of particles depends on factors including the chemical composition of the particle and the size and shape of the particle, and small particles composed of an inorganic material may have a lower sintering point compared to larger particles composed of the same inorganic material.

[0019] The described porous sintered body can be in the form of a porous sintered inorganic multilayer membrane. Different layers of the multilayer membrane contain different types of inorganic particles that function differently in providing the strength and filtering properties of the sintered membrane. The inner or "first" layer can function to provide significant strength to the sintered membrane and provide strength to the unsintered (green) form used to prepare the sintered porous membrane, and the first layer does not need to exhibit filtering properties (by sieving mechanism) for small particles, and can have pores of a size that allows a relatively high level of fluid flow through the first layer compared to a lower level of fluid flow through the second layer.

[0020] The outer, or "second," layer can add an additional amount of strength to the porous sintered membrane and also contains small pores formed by the sintered nanoparticles, acting as a sieve-type filtering layer.

[0021] The different layers contain at least three different types of inorganic particles, referred to as "coarse", "fine" and "nanoparticles", which may have different sizes, different compositions, different sintering points, or a combination thereof. Examples of inorganic particles useful as either the different types of particles of the first or second layers of the sintered membrane include inorganic particles that may be metal or ceramic. Metal particles may contain (may comprise, consist of, or consist essentially of) one or more metals, either as pure metals or alloys. Examples of metals include iron, refractory metals (e.g., tungsten, molybdenum, tantalum), titanium, and nickel. Examples of metal alloys include stainless steel, another iron or steel alloy, nickel alloy, titanium alloy, among others. Exemplary ceramics include metal oxides, such as zirconia (ZrO2), alumina (Al2O3), and the like. In accordance with a specific example film, the fine particles can be composed of the same material as the coarse particles, e.g., the fine particles of a film are composed of a metal or metal alloy, such as stainless steel, nickel, or a nickel alloy, and the coarse particles of the same film are composed of the same metal or metal alloy.

[0022] Particles referred to as "coarse" particles may be included in and may constitute a majority of the first membrane layer. The coarse particles may provide strength to the first layer and the sintered multilayer membrane, and may result in a first layer that has relatively large pores that allow relatively high fluid flow through the first layer, but does not provide a sieve-type filtering function for small scale (e.g., nanoscale) contaminants.

[0023] Coarse particles refers to a collection of small (micron-scale) particles that begin as raw material in powder form and typically have similar composition and varying sizes. The coarse particles used to produce the first layer may have a shape and size that allows the coarse particles to be useful in forming the described first layer based on the described methods where the particles are effective upon sintering to form the first layer of the porous sintered body.

[0024] Exemplary coarse particles may have particle sizes in the range of tens of microns, such as 10-200 microns, 10-150 microns, 10-100 microns, 25-200 microns, 25-150 microns, 25-100 microns, 25-75 microns, 50-200 microns, 50-150 microns, or any range or subrange therebetween. Particle size for metal and ceramic particles can be measured by ASTM B822-17 (Standard Test Method for Particle Size Distribution of Metal Powders and Related Compounds by Light Scattering).

[0025] Coarse particles can include shapes or surfaces that can be regular (e.g., consistent within the powder) or irregular, such as round or spherical, globular, branched, etc. Examples of useful coarse particles can be generally round, non-high aspect ratio particles in the multi-micron size range. The particles are typically round, non-dendritic, and do not exhibit high aspect ratios, e.g., average aspect ratios of less than 10, less than 5, or less than 4 or less than 3.

[0026] Examples of coarse particles used to form the first layer can be substantially or completely composed of (may comprise, consist of, or consist essentially of) ceramic, metal, or metal alloy, such as refractory metal, stainless steel, nickel, nickel alloy, for example, can contain at least 90, 95, 98, or 99 weight percent ceramic, metal (pure metal), or metal alloy, such as stainless steel, nickel, or nickel alloy. Coarse particles containing a large amount of stainless steel can have a sintering point in the range of 900-1200 degrees Celsius. Coarse particles containing a large amount of nickel or nickel alloy can have a sintering point in the range of 1000-1300 degrees Celsius. Coarse particles containing a large amount of ceramic or refractory metal (e.g., at least 90, 95, 98, or 99 weight percent ceramic or refractory metal) can have a sintering point above 1300 or 1400 degrees Celsius.

[0027] As used herein, a material or combination of materials that is said to "consist essentially of" a material or combination of materials will contain the material or combination of materials and no more than insignificant amounts of other materials, e.g., no more than 1, 0.5, or 0.1 weight percent of any other component, e.g., grit consisting essentially of nickel is composed of nickel and no more than 1, 0.5, or 0.1 weight percent of any other component.

[0028] Particles referred to as "fine" particles can be included in and comprise a majority of the first layer and a majority of the second layer. Fine particles can be smaller than coarse particles and larger than nanoparticles, e.g., having a particle size greater than 1 micron but less than 10 microns. Fine particles can function to provide strength, continuity, and integrity to the multilayer sintered membrane by being present in both the first and second layers, thereby providing a continuous sintered network that creates continuity and strength between the two layers.

[0029] In certain examples of the film, the fine particles may have the same chemical composition as the chemical composition of the coarse particles to facilitate sintering of the different sizes of the coarse particles and the fine particles in the first layer. The sintering point of the fine particles may be a temperature that is less than the sintering point of the coarse particles and less than the sintering point of the nanoparticles. In certain examples of the film, the fine particles may have a different chemical composition than the chemical composition of the nanoparticles to enable the fine particles to have a sintering point that is less than the sintering point of the nanoparticles.

[0030] The particulates in the first layer ("first particulates") may be the same or different in terms of particle size and particle composition as the particulates in the second layer ("second particulates"). In the example of a membrane, the first particulates may have the same chemical composition and the same size and shape (average size, size profile, shape and morphology (e.g., dendritic)) as the second particulates.

[0031] Exemplary particulates (first particulate and second particulate) may be in the form of a powder containing an aggregate of particles substantially or entirely composed of ceramic, metal (e.g., refractory metal, nickel), or metal alloy such as stainless steel, or nickel alloy, for example, at least 90, 95, 98, or 99 weight percent ceramic, refractory metal, stainless steel, nickel, or nickel alloy. Particulates containing a large amount of stainless steel may have a sintering point in the range of 900 to 1200 degrees Celsius, and the particulates contained in any particular sintered film have a sintering point below the sintering point of the coarse particles in the film. Particulates containing a large amount of nickel or nickel steel may have a sintering point in the range of 600 to 1100 degrees Celsius, and the particulates used in a particular sintered film have a sintering point below the sintering point of the coarse particles in the film. Particulates containing a large amount of ceramic or refractory metal (e.g., at least 90, 95, 98, or 99 weight percent ceramic or refractory metal) may have a sintering point above 1300 or 1400 degrees Celsius.

[0032] The particulates may be formed to have shapes or surfaces that may be regular (e.g., consistent within the powder) or irregular, e.g., round or spherical, globular, branched, elongated, dendritic, etc. In certain examples, the first and second particulates may be of the type sometimes referred to as highly anisotropic dendritic particles, such as those described in U.S. Pat. No. 5,814,272 ("the '272 patent"), the entirety of which is incorporated herein by reference.

[0033] According to the '272 patent, and as used herein, the term "dendritic" refers to a highly anisotropic, irregular particle morphology in which the particles have a structure that includes one, or typically multiple, filaments or branches, each of which individually has one dimension (of three dimensions) that is greater than the other two dimensions of the filament. One or more branches or filaments may be independently straight or curved, and may be branched or unbranched. Dendritic particles are characterized by a lower packing efficiency compared to particles of more regular morphology, and therefore form powders of lower apparent density compared to powders formed by particles made of similar chemical composition but with more regular (non-dendritic) morphology. Under magnification, dendritic particles may appear as aggregates or agglomerates of non-dendritic starting particles. See Figure 6 of the '272 patent.

[0034] Dendritic powders can be effective in forming free-standing precursors (e.g., green forms, see below) and sintered bodies of relatively low density and high porosity compared to precursors and sintered bodies constructed from comparable non-dendritic powders.

[0035] Dendritic particles may be formed by fusing together non-dendritic or partially dendritic particles that are part of a collection of particles of a powder. Briefly, a powder of dendritic particles may be formed by the methods described in the '272 patent. Thus, a powder of dendritic particles may be formed from a substantially non-dendritic powder by heating the non-dendritic powder under conditions suitable for an early stage of sintering to form a lightly sintered material. The lightly sintered material may then be treated to disrupt some of the sintered bonded particles to form dendritic particles. These steps may be repeated as desired.

[0036] The term "lightly sintered material" refers to a material produced by the fusion of metal powder particles going through the early stages of sintering as defined by Randall (Randall in "Powder Metallurgy Science", second edition, German, ed., Metal Powder Federation Industry (1994), the contents of which are incorporated herein by reference). In the early stages of sintering or short range diffusion sintering, bonds are formed between particles at their contact surfaces, and fusion of metal powder particles occurs only with directly adjacent particles. Thus, in the early stages of sintering, a weak structure with low mechanical strength results. For a given material, sintering proceeds gradually beyond this early stage at temperatures at the lower end of the sintering range of the material. For the purposes of this specification, the term "early stage sintering" refers to the sintering of a powder under conditions where sintering does not proceed substantially beyond the early stage.

[0037] The term "substantially non-dendritic particles" refers to particles that contain mostly or entirely (e.g., at least 80, 90, or 95 weight percent) particles having a non-dendritic morphology, e.g., in the form of a powder or as part of a green body or sintered film.

[0038] Particles called "nanoparticles" can be included in and make up the majority of the second layer to produce a second layer with pores small enough to remove very small (nanoscale) contaminants from the fluid by a sieving filtration mechanism. Nanoparticles are much smaller than coarse particles and smaller than fine particles, e.g., nanoparticles can have submicron particle sizes, e.g., less than 1.0 or 0.9 microns, e.g., in the range of 0.001 to 0.5 microns.

[0039] In a particular example film, the nanoparticles may have a chemical composition different from that of the coarse particles and different from that of the fine particles. Also, the nanoparticles may have a sintering point higher than that of the fine particles (both the first and second fine particles). The sintering point of the nanoparticles may be higher than that of the coarse particles, lower than that of the coarse particles, or about the same as that of the coarse particles.

[0040] The use of nanoscale inorganic particles in the second layer of the sintered membrane can produce a sintered membrane that can exhibit pore sizes in the nanometer range, for example, less than 50, 20, or 10 nanometers (e.g., as indicated by bubble points). If having nanoscale pore sizes, the sintered membrane can be effective in removing nanoscale particulate contaminants from a fluid by a sieving mechanism with a filter having pores smaller than the size of the contaminants.

[0041] Examples of nanoparticles of sintered membranes or precursors can be made substantially or completely of (may comprise, consist of, or consist essentially of) stainless steel, titanium or titanium alloys, refractory metals, ceramics such as zirconia (ZrO2) or alumina (Al2O3), for example, containing at least 90, 95, 98, or 99 weight percent stainless steel, titanium, titanium alloy, or ceramic. Nanoparticles containing a large amount of stainless steel may have a sintering point in the range of 800 to 1100 degrees Celsius, and the nanoparticles used in any particular sintered membrane have a sintering point that exceeds the sintering point of the first and second particulates of the sintered membrane. Nanoparticles containing a large amount of titanium, titanium alloy, or ceramic may have a sintering point in the range of 1000 to 1400 degrees Celsius, and the nanoparticles used in any particular sintered membrane have a sintering point that exceeds the sintering point of the first and second particulates of the sintered membrane. Nanoparticles that contain a large amount of ceramic or refractory metal (eg, at least 90, 95, 98, or 99 weight percent ceramic or refractory metal) can have a sintering point greater than 1300 or 1400 degrees Celsius.

[0042] The shape of the nanoparticles may include shapes or surfaces that may be regular (eg, consistent within a powder) or irregular, such as round or spherical, globular, branched, or non-dendritic.

[0043] Sintered membranes contain three different types of particles (coarse, fine, and nanoparticles) that, when present together in a multilayer membrane, provide a membrane with very fine pore sizes for filtering very fine particles, but also with high strength, comprising two visually distinct but physically interconnected layers. The different sizes, chemical configurations, and sintering points of the coarse, fine, and nanoparticle particles are selected to produce the desired combination of filtering effectiveness, strength properties, and processing (sintering) properties.

[0044] The first membrane layer includes fine particles (first fine particles) and coarse particles, and the chemical composition of the fine particles and coarse particles is preferably similar or identical. By selecting the fine particles and coarse particles to have similar or identical chemical composition, the ability of the particles to bond by sintering can be improved. The fine particles (first fine particles) of the first layer can also have a similar or identical chemical composition to the fine particles of the second layer to provide strength and physical continuity between the first layer and the second layer. In the example of the membrane, the first layer does not require nanoparticles and preferably does not contain nanoparticles, for example, contains less than 1, 0.5 or 0.1 weight percent nanoparticles.

[0045] The second layer includes a second particulate in combination with a smaller "nanoparticle" without the need for any coarse particles. The second particulate may have a similar or identical chemical makeup to the first particulate to provide strength and physical continuity between the first and second layers. The nanoparticle may have a different chemical makeup (chemical composition) compared to the first particulate, compared to the second particulate, and compared to the coarse particles.

[0046] The microparticles and nanoparticles of the second layer provide a combination of useful functions for the second layer. The nanoparticles, when sintered, define the desired small pore size for filtering nanoscale particles by sieving filtration mechanisms. The microparticles, especially if they are the same (size, chemical makeup) as the microparticles of the first layer, provide the desired processing, strength, and stability properties since both the microparticles of the first and second layers will experience similar levels of sintering, resulting in a physical connection between the first and second membrane layers.

[0047] The nanoparticles may also have a higher sintering point compared to the first and second fine particles, and in some cases may have a higher sintering point than the coarse particles. During processing (sintering), the nanoscale particles may only experience early stage sintering, while other particles are more completely sintered. Desirably, the nanoparticles do not experience any melting during sintering. Melting or excessive sintering may cause cracking or distortion of the second membrane layer, poor flow through the sintered membrane, and a lowered bubble point.

[0048] Selecting nanoparticles with a high sintering point compared to the first and second fine particles, and optionally a high sintering point compared to the coarse particles, can result in nanoparticles with a desirable relatively low sintering degree compared to the higher sintering degree of the fine and coarse particles. The low sintering degree of the nanoparticles allows for increased control of the filtering and flow properties of the sintered membrane, such as control of fluid flow as measured by pressure drop and increased pore size as measured by bubble point. Adjusting the relative amount of nanoparticles in the second layer of the membrane and the entire multilayer membrane can be useful to achieve the desired flow properties, pore size (for filtering), bubble point, etc.

[0049] The different layers can contain a range of useful amounts of the various types of particles. The first layer can contain effective relative amounts of coarse and fine particles. In one particular example, the first layer can comprise (can comprise, consist of, or consist essentially of) 50-70 weight percent coarse particles and 30-50 weight percent metal fine particles.

[0050] The second layer can contain any effective relative amounts of microparticles and nanoparticles. In one particular example, the second layer can comprise (can comprise, consist of, or consist essentially of) 40 to 75 weight percent microparticles and 25 to 60 weight percent nanoparticles.

[0051] The sintered membrane can contain any useful relative amounts of the first layer and the second layer. In one particular example, the sintered membrane can comprise (can comprise, consist of, or consist essentially of) 50 to 75 weight percent of the first layer and 25 to 50 weight percent of the second layer, based on the total weight of the sintered membrane.

[0052] The total membrane thickness and the relative thicknesses of the first and second layers of the membrane can be selected as desired. The first layer can have a thickness that provides support for the second layer without excessively restricting fluid flow through the body. The second layer can have a thickness that provides the desired filtering performance and can also contribute to the overall strength of the membrane, especially tubular membranes.

[0053] The total thickness of the porous sintered body for use as a filter membrane can be relatively thin, e.g., have a thickness that is relatively small in size. A relatively thinner filter membrane can provide certain desired properties of the filter membrane, including reduced mass and pressure drop across the filter during use. Examples of useful or preferred porous sintered membranes suitable for use as filter membranes, e.g., filter membranes in tubular form and useful for filtering supercritical fluids, can have a thickness of less than 1.5 or 2 millimeters, e.g., less than 1, 0.9 or 0.8 millimeters, e.g., in the range of 0.4 to 1 millimeter.

[0054] In the example of a porous sintered membrane, the first (coarse) layer may be thicker or thinner than the second layer. According to certain examples, the described membrane may have a first (coarse) layer thickness that is at least 50 percent of the total thickness of the body, for example, at least 55, 60, 70, or 80 percent of the total thickness of the body. The second layer may have a thickness that is up to 50 percent (i.e., 50 percent or less) of the total thickness of the body, for example, up to 20, 30, 40, 45, or 50 percent of the total thickness of the body.

[0055] The porous sintered membrane contains a first layer, a second layer, and may, but need not, contain other layers or materials. According to certain examples, the porous sintered body may be made to consist or consist essentially of the first and second layers. A porous sintered body "consisting essentially of" a first and second layer contains these two layers and no more than a minor amount of any other layer or material, for example, no more than 1, 0.5, or 0.1 weight percent of any other layer or material.

[0056] The described porous sintered membrane, and precursors thereof, comprises two (or more) identifiable portions or "layers" made of different types of particles. Without limiting the function of the different layers, the "first" layer may also be referred to herein as the "coarse layer" or "support layer", and the "second" layer may also be referred to as the "fine layer" or "filtering layer". The first layer is made of and comprises a combination or "blend" of coarse particles and a first fine particle, which is free of nanoparticles or substantially free of nanoparticles. The second layer is made of and comprises a combination or "blend" of a second fine particle and a nanoparticle, which is free of coarse particles or substantially free of coarse particles.

[0057] The two distinct layers can be visually detected using magnification. In the form of a sintered film, the first layer, which includes coarse and fine particles, can be considered to contain a combination of coarse particles bonded together at the particle surface by the sintering process, with fine particles bonded to coarse particles and other fine particles. The first layer has a relatively high porosity compared to the second layer and does not contain a significant amount of nanoparticles.

[0058] The second layer of the sintered film, which includes the second particulates and nanoparticles, can be considered to contain a combination of particulates and nanoparticles bonded together at the particle surfaces by the sintering process. The second layer has relatively lower porosity and does not contain a significant amount of coarse particles compared to the first layer.

[0059] 1 shows a schematic side, cross-sectional view of a portion of a porous sintered membrane as described. The membrane 10 includes a first layer 20 made mostly or entirely of coarse particles 22 and first fine particles 24. The membrane 10 includes a second layer 30 made mostly or entirely of second fine particles 26 and nanoparticles 28. The grains formed into the porous sintered membrane 10 are interconnected at the surfaces of the sintered particles.

[0060] Figure 2 is a photomicrograph image of the porous sintered membrane shown generally in Figure 1. Shown is a body membrane 10, a first layer 20 made mostly or entirely of coarse particles 22 and first fine particles 24, and a second layer 30 made mostly or entirely of second fine particles 26 and nanoparticles 28. The grains formed into the porous sintered membrane 10 are interconnected at the surfaces of the sintered particles.

[0061] Exemplary porous sintered bodies can be assembled and formed into sintered membranes of any useful size and configuration, for example, as flat sheets and three-dimensional shapes such as in the form of rounded cups, cones, open tubes (open at two opposite ends), or closed-ended tubes (also known as "closed cylinders" meaning tubes or cylinders having one closed end and one open end). A specific example of a filter body useful for filtering supercritical carbon dioxide can be an open cylindrical filter membrane, i.e., a tube having a length in the range of 10 to 100 millimeters and a diameter in the range of 0.5 to 2 inches, e.g., 0.75 to 1.5 inches.

[0062] The porous sintered membrane and each of its layers can have properties that enable the membrane to be useful as a filtering membrane, including porosity, bubble point (indicating pore size), air flow, and strength (for tubular filter membranes, strength can be measured using a radial crush test).

[0063] The first and second layers of the described membranes may have porosity values ​​that allow the layers, in combination, to be effective for a desired use, for example as a filter membrane. According to a useful example, the first layer of the described porous sintered body may have a porosity of at least 40 percent, for example a porosity in the range of 35 to 60 percent. The second layer of the porous sintered membrane may have a porosity in the range of about 15 to about 30 percent.

[0064] As used herein, and in the art of porous sintered bodies, the "porosity" (also sometimes referred to as void fraction) of a porous sintered body is a measure of the void (i.e., "empty") space in the body as a percentage of the total volume of the body, calculated as the fraction of the volume of the voids in the body relative to the total volume of the body. A body with zero percent porosity is completely solid.

[0065] The sintered membranes herein may have a useful bubble point that allows the body to be effective in filtering fluids, such as supercritical fluids, such as supercritical carbon dioxide. Examples of useful or preferred bubble points of the membranes may be at least 25, 30, 40, or 45 pounds per square inch (psi) as measured by bubble point test method ASTM E128-99(2019) using a 60 / 40 mixture (by volume) of isopropyl alcohol (IPA) and water.

[0066] The sintered membranes herein having a tubular shape can have a strength to withstand a pressure of at least 20, 25, 30, 35, 40, or 45 kilopounds per square inch (ksi) as measured by the radial compression test (ASTM B939-21).

[0067] Sintered membranes herein having a tubular shape can have an "air flux" of at least 0.03, 0.04, 0.05, 0.06, 0.07, or 0.08 standard liters per minute (slpm) per square centimeter, measured at 30 pounds per square inch pressure.

[0068] For example, the described porous bodies prepared and used as filter membranes for filtering supercritical carbon dioxide will exhibit comparable or improved filtering and flow properties compared to previous porous sintered filter membranes. The described filter membranes, particularly tubular filter membranes, can exhibit a useful combination of airflow, bubble point, and strength, or an improved combination of two or more of these, compared to porous sintered filter membranes that do not include the two specific layers described herein made from the three specific inorganic particles.

[0069] Without being bound by theory, the different types of particles in the first and second layers are effective to provide a useful or even advantageous combination of strength, airflow, and filtering properties (e.g., small pore size, desired bubble point, and strength). The coarse particles in the first membrane layer are effective to impart a high degree of strength to the sintered membrane, the nanoparticles in the second layer are effective to provide effective filtering (small pore size, relatively high bubble point); the fine particles present in both the first and second layers provide additional strength and integrity by providing a sintered network of particles connecting the first layer with the second layer.

[0070] The described porous sintered body can be used as a filter membrane to remove particulate contaminants having nanometer-scale particle sizes from a fluid stream conducted through the filter membrane. The fluid can be any type of fluid, including gas, liquid, or supercritical fluid. The fluid can be any fluid that requires filtration to remove nanoscale particulate contaminants, including supercritical carbon dioxide containing low levels of particulate impurities from any source, as a specific example.

[0071] Supercritical carbon dioxide is useful for processing or fabricating semiconductor and microelectronic devices. Porous sintered membranes can be effective in removing particulate contaminants from fluid streams by sieving or non-sieving filtering mechanisms or both. Advantageously, filter membranes containing sintered nanoparticles, such as those described as part of the second layer, can include pores formed between the sintered nanoparticles that are small enough to allow the membrane to remove nanoscale particles by sieving mechanisms, such as removing contaminant particles with a particle size of less than 50, 20, 10 nanometers by physically preventing the particles from passing through the membrane pores that are smaller than the size of the contaminant particles.

[0072] The pressure of the fluid processed by the filtering system including the sintered membrane described can be relatively low or relatively high. For certain types of methods and devices used to filter fluids including supercritical carbon dioxide, the pressure of the fluid inside the filtering system, e.g., the fluid passing through the filter membrane, is relatively high, e.g., at least 10, 20, or even up to 30 megapascals (MPa) or more.

[0073] The pressure difference (or "pressure drop") across the thickness of the described filter membrane (between the upstream side of the filter and the downstream side of the filter) during use of the filter membrane can be any pressure difference that allows for the desired effectiveness (e.g., particle retention) during the filtering process (e.g., for a given flow rate of fluid) and is also commercially viable. In the use of the described sintered membranes, to filter supercritical carbon dioxide at high pressure, the difference across the filter membrane can be at least 1, 2, or 3 megapascals (MPa).

[0074] The amount of fluid flowing through the filter membrane during the filtering process (volume / time through the filter) can be an amount that allows for the desired effectiveness (e.g., particle retention) during the filtering process and is also commercially viable.

[0075] The temperature of the fluid stream through the described filter membranes can be any temperature that allows for commercially effective filtering. For filtering supercritical carbon dioxide, the temperature can be relatively high, for example at least 100, 150 or 200 degrees Celsius.

[0076] The described sintered membranes can be prepared by a multi-step process of forming a precursor containing a first layer of the described particle combination and a second layer of the particle combination as described, followed by sintering the precursor to bond the particles of the layers together to form a porous sintered membrane.

[0077] In one particular example method, the precursor may be formed by a dry method using a dry powder of metal particles, without the need for any polymer or other liquid components to be present inside the powder. The first layer of the precursor may be formed by molding the first layer from a first dry powder that includes (comprises, consists of, or consists essentially of) a blend of coarse and fine particles to form a green body of the first layer, for example, using an isotactic molding technique. After the green body of the first layer is formed, a dry powder containing (comprises, consists of, or consists essentially of) a blend of fine and nanoparticles as described for the second layer is applied uniformly to the green body surface of the first layer and compressed against the surface again by an isotactic molding technique. The resulting green body having a first (coarse) layer and a second (fine) layer is then sintered to produce a sintered porous body having a first layer and a second layer as described herein. Each of the green body and its two separate layers consists of or consists essentially of the layers produced from the powder, and may not require or include any other materials such as polymers (binders), surfactants, solvents, etc.

[0078] According to one example process, a collection of particles in dry powder form, mostly or entirely containing a blend of coarse and fine particles (first particulates), is molded under pressure to compress the particles to form a thin film, e.g., a thin film in the form of small tubes. According to one technique, the molding process can be of the type referred to as isotactic molding, or isotactic wet pressing. (See, for example, U.S. Pat. No. 7,534,287, which is incorporated herein by reference in its entirety). The resulting film will contain mostly or entirely a blend of coarse and fine particles compressed together by the molding process, and will be the first layer of the porous sintered body. The thin film is held together by the contacts created between the particles by the compression of the particles. The thin film, referred to as the "precursor" or "green body," but specifically herein as the "precursor of the first layer," is self-supporting but fragile.

[0079] The second blend of particles contains (consists of, or consists essentially of) a blend of particulates ("second" particulates) and nanoparticles in large part or in entirety. This blend of particles is applied to one surface of the first layer precursor, for example, to the outer surface of the first layer precursor in the form of a tube. The second blend is applied so as to place a uniform and homogeneous amount of the blend on the surface of the first layer precursor. Effective methods of applying the blend of particles to the surface of the first layer precursor are known and include methods referred to as "air laying" techniques, such as placing a screen or mesh over the surface of the first layer, then passing the blend of particles through the screen, and optionally using a brush to distribute the particles evenly.

[0080] After disposing the second blend of particles evenly across the surface of the first layer, the resulting body is again molded under pressure to compress the particles of the second blend to form a compressed second layer on the surface of the first layer. The molding and compression of the second blend of particles on the surface of the first layer can be performed by an isotactic molding technique, for example, an isotactic wet pressing technique. The resulting precursor ("green body") contains a compressed, unsintered first layer made from a blend of coarse particles and a first fine particle, and a compressed, sintered second layer made from a second blend containing fine particles and nanoparticles.

[0081] In a subsequent step, the precursor is sintered at a sintering temperature that will be effective to bond the particles of both layers into a single porous sintered body. During sintering, the fine particles begin to sinter first before the coarse particles begin to sinter and before the nanoparticles begin to sinter. The first fine particles of the first layer and the second fine particles of the second layer preferably experience a similar level of sintering during the sintering step, which provides stability to the sintered film and can prevent cracking and distortion of the film.

[0082] The nanoparticles and coarse particles begin to sinter at a temperature (sintering point) above the sintering point of the first fine particles and the sintering point of the second fine particles (these sintering points may be the same). The nanoparticles may optionally begin to sinter before (at a lower temperature) or after (at a higher temperature) the coarse particles begin to sinter. During sintering, the nanoscale particles may only experience early stage sintering, while the other particles sinter more completely. Desirably, the nanoparticles do not experience any melting during sintering.

[0083] The porous sintered membrane may be included in a filtering system or device that includes a filter housing that contains and supports the filter membrane at a location of fluid flow such that as fluid passes through the filter housing, the fluid flows through the membrane. The filter housing may have an inlet, an outlet, and an interior volume that contains the filter membrane.

[0084] An example filter housing (cross section) is shown in Figure 3. The example filter housing 100 includes a housing body 110, a fluid inlet 112, a fluid outlet 114, and an interior 120. A tubular multi-layer porous sintered body 130 is contained in the interior 120, for example, by welding to a housing base 124 at joint 130. In use, fluid (not shown) flows through the filter membrane 130 through the interior 120, as represented by the arrow to the inlet 112, and exits the filter housing through the outlet 114.

[0085] The described tubular filter membrane examples can withstand the pressure differentials used in the supercritical carbon dioxide filtering process without breaking, distorting, or being physically impaired for useful product life. One method for determining the strength of the porous sintered tubular filter membrane is by what is called a radial compression test, which is performed according to ASTM B939-21. This test shows that a multi-layer sintered membrane in the form of a tubular membrane having two layers made from the sintered particles described herein can withstand at least 25, 30, 35, 40, or 45 kilopounds per square inch (ksi) when tested using a radial compression crush test. EXAMPLES

[0086] Example 1 - Preparation of sintered membrane The multi-layer porous sintered membrane is prepared by a multi-step process including the following: a first step for preparing a first (inner) unsintered membrane layer (first layer green body), followed by a second step for providing a second (outer) unsintered layer on the outer surface of the first unsintered layer, and then sintering the bilayer precursor to form a sintered monolithic inorganic (e.g., metallic) bilayer composite asymmetric nanoporous tubular sieving membrane.

[0087] The first layer is a blend of 1-5 micron ("fine") dendritic particles and 50-75 micron ("coarse") particles of the same chemical composition, with approximately 50 percent by weight of each type of particle. A rubber tubular isotactic mold with a central steel mandrel is filled with the blend of the two particles and pressed with sufficient pressure to form a coherent green form.

[0088] The second layer is made from a blend of particles including 1-5 micron ("fine") non-dendritic particles and 30-150 nanometer ("nanoparticles"), where the nanoparticles are of a different chemical composition than the microparticles. The two different particles are combined to form a blend containing approximately 50 weight percent of each of the two different types of particles. The blend is dispensed into a rubber isotactic tubular mold with the green form from the previous step acting as a central mandrel and pressed at a pressure to form a coherent green form and define the tightness (pore size) of the porous matrix to be further constructed.

[0089] The resulting bilayer green morphology precursor is sintered in a suitable atmosphere (compatible with the materials used) with sufficient heat input to sinter all materials to adjacent materials and to themselves, but not enough to oversinter or melt the pore-defining nanoparticles.

[0090] Example 2 - Performance of sintered membrane TIFF2025514135000002.tif76170 Example membranes prepared according to the present disclosure may exhibit relatively high bubble points (reduced pore size) compared to existing commercially available products while maintaining or exceeding strength as measured by radial compression testing or flux (flow rate / area) of tubular designs.

[0091] Examples A and B are tubular inorganic porous membranes prepared as described in U.S. Patent No. 7,534,287. Examples A and B were prepared from nickel particles that contained dendritic fine and nanoparticles but no coarse particles (as that term is used herein). The membranes of Examples A and B included an inner layer prepared from only dendritic nickel fine particles, and an outer layer prepared from a blend of dendritic nickel fine particles and nickel nanoparticles.

[0092] The membrane of Example 1 (this disclosure) has lower strength compared to the membrane of Example B, but Example 1 exceeds Example B in both flux and bubble point. Similarly, the flux of the membrane of Example 1 is lower than that of Example A, but the membrane of Example 1 has higher strength and bubble point. As can be seen in the table above, the porous membranes disclosed herein can achieve a combination of a bubble point of at least 30 psi, an air flux of at least 0.07 slpm / cm2 at 30 psi, and a radial compression crush test value of at least 35 kilopounds per square inch.

[0093] The porous membrane of the first embodiment includes a first layer including a combination of sintered inorganic particles including coarse particles having a particle size of at least 10 microns and a coarse particle sintering point, and first fine particles having a particle size of at least 1 micron and a first fine particle sintering point less than the coarse particle sintering point, a second layer including a combination of sintered inorganic particles including second fine particles having a particle size of at least 1 micron and a second fine particle sintering point less than the coarse particle sintering point, and nanoparticles having a particle size less than 1 micron and a nanoparticle sintering point greater than the first fine particle sintering point and greater than the second fine particle sintering point.

[0094] In a second embodiment of the first embodiment, the coarse particles have a particle size in the range of 10 to 200 microns.

[0095] In a third embodiment according to the previous embodiment, the first fine particles have a particle size in the range of 1 to 10 microns, and the second fine particles have a particle size in the range of 1 to 10 microns.

[0096] In a fourth embodiment according to the previous embodiment, the nanoparticles have a size in the range of 0.001 to 0.5 microns.

[0097] In a fifth embodiment according to the previous embodiment, the first particulate comprises nickel or a nickel alloy, the second particulate comprises nickel or a nickel alloy, the coarse particles comprise nickel or a nickel alloy, and the nanoparticles comprise stainless steel.

[0098] In a sixth aspect of the fifth aspect, the first microparticle sintering point is in the range of 600-1100 degrees Celsius, the second microparticle sintering point is in the range of 600-1100 degrees Celsius, the coarse particle sintering point is in the range of 900-1200 degrees Celsius, and the nanoparticle sintering point is in the range of 800-1100 degrees Celsius.

[0099] In a seventh aspect according to any of the first to fourth aspects, the first particulate comprises stainless steel, the second particulate comprises stainless steel, the coarse particle comprises stainless steel, and the nanoparticles comprise titanium, a titanium alloy, alumina, or zirconia (ZrO2).

[0100] In an eighth aspect of the seventh aspect, the first microparticle sintering point is in the range of 900-1200 degrees Celsius, the second microparticle sintering point is in the range of 900-1200 degrees Celsius, the coarse particle sintering point is in the range of 1000-1300 degrees Celsius, and the nanoparticle sintering point is in the range of 1000-1400 degrees Celsius.

[0101] In a ninth embodiment according to the previous embodiment, the first layer comprises 50 to 70 percent by weight of the coarse particles and 30 to 50 percent by weight of the first fine particles.

[0102] In a tenth embodiment according to the previous embodiment, the second layer comprises 40 to 75 weight percent of the second microparticles and 25 to 60 weight percent of the nanoparticles.

[0103] In an eleventh embodiment according to the previous embodiment, there is between 50 and 75 weight percent of the first layer, and between 25 and 50 weight percent of the second layer.

[0104] In a twelfth embodiment according to the previous embodiment, the first microparticle is dendritic and the second microparticle is dendritic.

[0105] In a thirteenth embodiment according to the previous embodiment, the membrane comprises a tube.

[0106] In a fourteenth aspect according to the thirteenth aspect, the tube has a diameter in the range of 0.5 to 2 inches.

[0107] In a fifteenth aspect according to the thirteenth or fourteenth aspect, the membrane has a radial compression test value of at least 30 kilopounds per square inch when tested according to ASTM B939-21.

[0108] In a sixteenth aspect of the previous aspect, the membrane has a bubble point of at least 25 pounds per square inch as measured by ASTM E 128-99(2019) measured using 60 / 40 isopropyl alcohol (IPA) / water.

[0109] In a seventeenth aspect, a filter assembly comprises a filter housing containing the filter membrane of any of the previous aspects.

[0110] In an eighteenth method of processing supercritical carbon dioxide, the method comprises passing supercritical carbon dioxide through the membrane of any of the previous embodiments.

[0111] In a nineteenth method of forming a porous membrane, the method includes preparing a precursor comprising a first blend of inorganic particles including coarse particles having a particle size of at least 10 microns and a coarse particle sintering point, and a first particulate having a particle size of at least 1 micron and a first particulate sintering point less than the coarse particle sintering point, and applying a second blend of inorganic particles to a surface of the precursor, the second blend including second particulates having a particle size of at least 1 micron and a second particulate sintering point less than the coarse particle sintering point, and nanoparticles having a particle size less than 1 micron and a nanoparticle sintering point greater than the first particulate sintering point and greater than the second particulate sintering point.

[0112] In a twentieth aspect described in the nineteenth aspect, the method further includes compressing the first blend of metal particles to form a first green body, applying a second blend of metal particles to the first green body, compressing the first green body and the second blend of metal particles to form a second green body, and sintering the second green body.

[0113] In a twenty-first aspect described in the twentieth aspect, the sintering includes increasing the temperature of the second green body such that the first fine particles and the second metal fine particles begin to sinter before the coarse metal particles begin to sinter, and the fine particles begin to sinter before the nanoparticles begin to sinter.

[0114] In a twenty-second embodiment according to the twenty-first embodiment, the coarse particles start sintering before the nanoparticles.

[0115] In a twenty-third aspect according to any of the nineteenth to twenty-second aspects, the membrane comprises a tube.

[0116] In a twenty-fourth aspect according to the twenty-third aspect, the tube has a diameter in the range of 0.5 to 2 inches.

[0117] In a twenty-fifth aspect according to the twenty-third or twenty-fourth aspect, the membrane has a radial compression test value of at least 30 kilopounds per square inch when tested according to ASTM B939-21.

[0118] In a twenty-sixth aspect according to the twenty-third, twenty-fourth or twenty-fifth aspect, the membrane has a bubble point of at least 25 pounds per square inch as measured by ASTM E 128-99(2019) measured using 60 / 40 isopropyl alcohol (IPA) / water.

[0119] In a twenty-seventh embodiment, a tubular porous membrane comprises coarse particles having a particle size of at least 10 microns, fine particles having a particle size of at least 1 micron, and nanoparticles having a particle size of less than 1 micron, wherein the porous membrane has a bubble point as measured by ASTM E 128-99(2019) of at least 30 pounds per square inch, an air flux value at 30 psi of at least 0.07 slpm / cm2, and a radial compression test value of at least 35 kilopounds per square inch as measured using 60 / 40 isopropyl alcohol (IPA) / water.

[0120] In a 28th embodiment described in the 27th embodiment, the membrane further comprises a first layer comprising a combination of sintered inorganic particles comprising coarse particles having a particle size of at least 10 microns and first fine particles having a particle size of at least 1 micron, and a second layer comprising a combination of sintered inorganic particles comprising second fine particles having a particle size of at least 1 micron and nanoparticles having a particle size of less than 1 micron.

[0121] In a twenty-ninth aspect according to the twenty-seventh or twenty-eighth aspect, the membrane comprises a tube having a diameter in the range of 0.5 to 2 inches.

Claims

1. 1. A porous membrane comprising: coarse particles having a particle size of at least 10 microns and a coarse particle sintering point; and a first particulate having a particle size of at least 1 micron and a first particulate sintering point less than the coarse particle sintering point; A first layer comprising a combination of sintered inorganic particles comprising: a second particulate having a particle size of at least 1 micron and a second particulate sintering point less than the coarse particle sintering point; and Nanoparticles having a particle size less than 1 micron and having a nanoparticle sintering point greater than a first microparticle sintering point and greater than a second microparticle sintering point. A second layer comprising a combination of sintered inorganic particles comprising A porous membrane comprising:

2. The membrane of claim 1, wherein the coarse particles have a particle size in the range of 10 to 200 microns.

3. The membrane of claim 1 or 2, wherein the first particulate has a particle size in the range of 1 to 10 microns and the second particulate has a particle size in the range of 1 to 10 microns.

4. The membrane of any of claims 1 to 3, wherein the nanoparticles have a size in the range of 0.001 to 0.5 microns.

5. the first particulate comprises nickel or a nickel alloy; the second particulate comprises nickel or a nickel alloy; and the coarse particles comprise nickel or a nickel alloy; The membrane of claim 1 , wherein the nanoparticles comprise stainless steel.

6. the first particulate sintering point is in the range of 600-1100 degrees Celsius; a second particulate sintering point in the range of 600 to 1100 degrees Celsius; The coarse grain sintering point is in the range of 900 to 1200 degrees Celsius; and 6. The film of claim 5, wherein the nanoparticle sintering point is in the range of 800 to 1100 degrees Celsius.

7. the first particulate comprises stainless steel; the second particulate comprises stainless steel; the coarse particles include stainless steel; and The nanoparticles are made of titanium, titanium alloy, alumina, or zirconia (ZrO 2 5. The membrane of claim 1 , comprising:

8. the first particulate sintering point is in the range of 900-1200 degrees Celsius; a second particulate sintering point in the range of 900-1200 degrees Celsius; The coarse grain sintering point is in the range of 1000 to 1300 degrees Celsius; and 8. The film of claim 7, wherein the nanoparticle sintering point is in the range of 1000 to 1400 degrees Celsius.

9. The first layer is 50 to 70 weight percent coarse particles, and The membrane of any one of claims 1 to 8, comprising 30 to 50 weight percent of the first particulate.

10. The second layer is 40 to 75 weight percent of a second particulate, and The membrane of any one of claims 1 to 9, comprising 25 to 60 weight percent nanoparticles.

11. 50 to 75 weight percent of the first layer, and The membrane of any one of claims 1 to 10, comprising 25 to 50 weight percent of the second layer.

12. the first microparticle is dendritic; and The membrane of claim 1 , wherein the second particulate is dendritic.

13. The membrane of claim 1 , wherein the membrane comprises a tube.

14. The membrane of claim 13, wherein the tube has a diameter in the range of 0.5 to 2 inches.

15. 15. The membrane of claim 13 or 14, wherein the membrane has a radial compression test value of at least 30 kilopounds per square inch when tested according to ASTM B939-21.

16. 16. The membrane of any one of claims 1 to 15, wherein the membrane has a bubble point of at least 25 pounds per square inch as measured by ASTM E 128-99(2019) measured using 60 / 40 isopropyl alcohol (IPA) / water.

17. A filter assembly comprising a filter housing containing a filter membrane according to any one of claims 1 to 16.

18. 18. A method for treating supercritical carbon dioxide, comprising passing the supercritical carbon dioxide through a membrane according to any one of claims 1 to 17.

19. 1. A method of forming a porous membrane, comprising: coarse particles having a particle size of at least 10 microns and a coarse particle sintering point; and a first particulate having a particle size of at least 1 micron and a first particulate sintering point less than the coarse particle sintering point; preparing a precursor comprising a first blend of inorganic particles comprising: applying a second blend of inorganic particles to the surface of the precursor, the second blend comprising: a second particulate having a particle size of at least 1 micron and a second particulate sintering point less than the coarse particle sintering point; and and comprising nanoparticles having a particle size of less than 1 micron and a nanoparticle sintering point greater than a first microparticle sintering point and greater than a second microparticle sintering point.

20. compressing the first blend of inorganic particles to form a first green body; applying a second blend of inorganic particles to the first green body; compressing the first green body and a second blend of inorganic particles to form a second green body; 20. The method of claim 19, further comprising sintering the second green body.

21. Sintering is the first fine particles and the second fine particles start sintering before the coarse particles start sintering; such that the first and second particulates begin to sinter before the nanoparticles begin to sinter, The method of claim 20 including increasing the temperature of the second green body.

22. 22. The method of claim 21, wherein the coarse particles begin to sinter before the nano particles.

23. 23. The method of any one of claims 20 to 22, wherein the membrane comprises a tube.

24. The method of claim 23, wherein the tube has a diameter in the range of 0.5 to 2 inches.

25. 25. The method of claim 23 or 24, wherein the membrane has a radial compression test value of at least 30 kilopounds per square inch when tested according to ASTM B939-21.

26. 26. The method of any one of claims 23 to 25, wherein the membrane has a bubble point of at least 25 pounds per square inch as measured by ASTM E 128-99(2019) measured using 60 / 40 isopropyl alcohol (IPA) / water.

27. A tubular porous membrane comprising: coarse particles having a particle size of at least 10 microns; a particulate having a particle size of at least 1 micron; nanoparticles having a particle size of less than 1 micron; The porous membrane is a bubble point of at least 30 pounds per square inch as measured by ASTM E 128-99 (2019) using 60 / 40 isopropyl alcohol (IPA) / water; an air flux value of at least 0.07 slpm / cm2 at 30 psi; and A radial compression test value of at least 35 kilopounds per square inch measured using ASTM B939-21; A tubular porous membrane having a

28. coarse particles having a particle size of at least 10 microns; and A first particulate having a particle size of at least 1 micron. A first layer comprising a combination of sintered inorganic particles comprising: a second particulate having a particle size of at least 1 micron; and Nanoparticles having a particle size of less than 1 micron A second layer comprising a combination of sintered inorganic particles comprising 28. The membrane of claim 27, further comprising:

29. The membrane of claim 27 or 28, wherein the membrane comprises a tube having a diameter in the range of 0.5 to 2 inches.

Citation Information

Patent Citations

  • Metallic porous body and its manufacture

    JP1991226534A

  • Porous sintered compact

    JP2003129111A

  • Sintered porous material comprising particles of different average sizes

    JP2012530592A

  • Composite nanoporous metal membranes

    JP2022513464A

  • Filter and manufacturing method thereof

    WO2006004011A1